An investigation on the falling film thickness of sheet flow over a completely wetted horizontal round tube surface. Issue 35 (26th July 2016) - Qiu, Qinggang; Zhu, Xiaojing; Mu, Lin; Shen, Shengqiang
Abstract: An investigation was performed to analyze the liquid film distributions of sheet flow on the surface of a horizontal round tube in a falling film evaporator using the commercial computational fluid dynamic code Fluent 6.3.26. A two-dimensional multi-phase flow model was developed under adiabatic condition. The temporal variation of flowing process of sheet flow and the steady film thickness distribution in the circumferential direction were analyzed in detail. The main objective has focused on the effects of multiple factors on the film thickness distribution. It was found that the whole process of liquid film flowing along the horizontal tube surface includes the transient sub-process and steady-state sub-process, and the former can be divided into five stages to be analyzed. The obviously asymmetric distribution of film thickness, which is contradictory to the Nusselt theory, is captured by the simulation results. Multiple factors have effects on the film thickness distribution. The film thickness increases with the increase in film Reynolds number. The big inter-tube spacing is capable of inducing high momentum and increasing the impact velocity of liquid film on the top of the tube, which results in the thinner distribution of liquid film layer around the perimeter of the horizontal tube. The film thickness becomes thinner as tube diameter increases. The effect of tube diameter is minor and the further increment of tube diameter shows few values to the improvement of heat and mass transfer.